2015
DOI: 10.1021/acsami.5b01478
|View full text |Cite
|
Sign up to set email alerts
|

Optically Tunable Chiral Plasmonic Guest–Host Cellulose Films Weaved with Long-range Ordered Silver Nanowires

Abstract: Plasmonic materials with large chiroptical activity at visible wavelength have attracted considerable attention due to their potential applications in metamaterials. Here we demonstrate a novel guest-host chiral nematic liquid crystal film composed of bulk self-co-assembly of the dispersed plasmonic silver nanowires (AgNWs) and cellulose nanocrystals (CNCs). The AgNWs-CNCs composite films show strong plasmonic optical activities, that are dependent on the chiral photonic properties of the CNCs host medium and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 45 publications
0
53
0
Order By: Relevance
“…Cholesteric assembly of CNCs allows for control of chiral lightmatter interactions in photonic structure that is not only relevant for fundamental aspects but also for practical interests. [37][38][39] To highlight the wrinkle-induced iridescence, we chose CWF4 as an ideal example due to its cholesteric photonic band-gap was far away from the visible range. When a collimated white light beam impinged on the film surface and aligned with a surface wrinkle perpendicular to the plane of light incidence, it exhibited a striking rainbow-like appearance that derived from the grating-induced light interference ( Figure 4A).…”
Section: Resultsmentioning
confidence: 99%
“…Cholesteric assembly of CNCs allows for control of chiral lightmatter interactions in photonic structure that is not only relevant for fundamental aspects but also for practical interests. [37][38][39] To highlight the wrinkle-induced iridescence, we chose CWF4 as an ideal example due to its cholesteric photonic band-gap was far away from the visible range. When a collimated white light beam impinged on the film surface and aligned with a surface wrinkle perpendicular to the plane of light incidence, it exhibited a striking rainbow-like appearance that derived from the grating-induced light interference ( Figure 4A).…”
Section: Resultsmentioning
confidence: 99%
“…They confirmed that the composite film had chiral nematic phase and Au NPs were incorporated in the host CNC matrix, through polarized optical microscopy (POM) and SEM analysis. In a further research by Ding et al., silver nanowires (Ag NWs) with a high aspect ratio, which had a weak liquid crystalline property by itself, were introduced to achieve coalignment of CNC nanorod and Ag NW in a chiral nematic phase . Ag NWs‐CNC composite film with a long‐range chiral ordering of the Ag NWs presented a strong plasmonic CD response in near ultraviolet and visible region.…”
Section: Macromolecule‐assisted Chiral Assembly Of Nanoparticlesmentioning
confidence: 99%
“…Low‐magnification scanning electron microscopy (SEM) images of the LCB hydrogel clearly demonstrated the preservation of spherical shape, a smooth surface at the bubble inner‐interface and a repeating lamellar‐like structure perpendicular to its surface (Figure b). In the chiral nematic‐ordered LCBs, the CNCs were retained in the lamellar bubble interface region with a twisting in a left‐handed direction,,, indicating that the bubble film was in a chiral nematic order, with the helical director perpendicular to the film surface (Figure c,d). However, in the case of nematic‐ordered LCBs, SEM analyses revealed that the rod‐like CNCs were highly aligned, with planar anchoring (Figure e).…”
Section: Figurementioning
confidence: 99%